Removal of phenolic compounds through overliming for enhanced saccharification of wheat straw. Issue 10 (17th May 2018) - Haq, Ikram; Arshad, Yesra; Nawaz, Ali; Aftab, Muhammad; Rehman, Asad; Mukhtar, Hamid; Mansoor, Zinnia; Syed, Qurratulain
Abstract: BACKGROUND: The deactivation of cellulases by phenolics is considered to be the main bottleneck in the saccharification of agricultural by‐products for efficient bioethanol production on a large scale. The removal of these phenolic inhibitors, produced as a result of pretreatment, is essential for an efficient saccharification process. One such process is overliming that has been mostly studied for hydrolysates of agricultural by‐products. In the present study however, solid biomass was used whereby the detection of phenolic compounds and their effect on saccharification was studied. RESULTS: The pretreated wheat straw showed 19% saccharification and total phenolic content (TPC) of 188 mg gallic acid equivalent g ‐1 biomass dry weight. Detoxification of pretreated wheat straw applying different alkalis, i.e. NaOH, NH4 OH and Ca(OH)2 was conducted. Overliming using Ca(OH)2 solution of pH 12, for 2 h at 80°C showed significant removal of 60% of phenolic compounds, which in turn enhanced the saccharification by 2.4‐fold. Scanning electron microscopy of pretreated and overlimed substrates also showed considerable change in structure, making it more accessible for enzymatic hydrolysis. CONCLUSION: The elimination of phenolic compounds due to overliming has facilitated increased saccharification that in turn will help in substrate efficient biofuel production. © 2018 Society of Chemical Industry